Analysis of Marketing Strategies in Improving Service Quality at Aska Printing and Photocopy Services - Siregar, Nur Wahyuni; Ratih Amelia; Charles Barkley; Agus Susanto; Zakia Fadila (Journal of Business Integration Competitive, 2025)
Marketing strategy is a critical component in increasing sales and competitiveness of both goods and services. This study aims to analyze marketing strategies in improving service quality at Percetakan and Fotocopy Aska, a printing business operating in a highly competitive area near university campuses in Medan. A qualitative approach was employed through interviews, observations, and documentation, with data analyzed using the SWOT method to identify the company's strengths, weaknesses, opportunities, and threats. The findings indicate that the overall service quality is rated as good, particularly in reliability and responsiveness. However, the assurance aspect received lower ratings and requires improvement. Promotional efforts through social media platforms such as WhatsApp, Instagram, and Facebook have proven effective in attracting new customers and maintaining the loyalty of existing ones. This study concludes that implementing appropriate marketing strategies and continuously enhancing service quality are essential to sustaining and growing printing service businesses in a competitive environment.